Clinico-epidemiological profile and complications of hand foot mouth disease among cases attending tertiary care centre in Northern Kerala, India - Linu, Mary; Thomas, Renu; Anandabhavan Kumaran , Jayasree (International Journal Of Community Medicine And Public Health, 2023)
Background: Hand-Foot-Mouth Disease (HFMD), has suddenly become more prevalent than ever in Kerala and is reported in almost all districts. Earlier studies showed EnteroVirus-A71 to be the causative agent, but frequent outbreaks are also caused by coxsackievirus A6 and A16. In 2022 there was a surge in the HFMD cases being reported to the institution with few cases requiring hospital admission due to complications. Methods: Study was a hospital based descriptive study in Government Medical College, Kannur, Kerala, India among Paediatric cases of HFMD, presented to the institution from April to July, 2022. Data was collected by direct interview using a semi structured questionnaire. It was coded and entered in MS Excel and analysed using SPSS 21. Results: Of the total 50 cases studied, 60% of the cases were in the age group of 1-3 years. Majority (58%) were females, with maximum cases being reported in the month of May. 32% had contact history with 18% being family contacts. Fever (72%), lesions on the hand (86%), foot (92%) and oral cavity (68%) were the most common clinical presentation. Complications developed in 10% of the cases, requiring hospital admission. Most common complication being neurological complication- acute cerebellar ataxia and atypical febrile seizure. A major factor noted among the cases that developed complications was that all were having chronic malnutrition. Conclusions: Even though majority of the cases had uncomplicated course, 10% cases showed complications. Therefore, awareness should be made regarding chances of complications and its risk factors. Assessment of nutritional status should be done in all cases.